2018
DOI: 10.1186/s12943-018-0920-z
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA LINC00312 induces lung adenocarcinoma migration and vasculogenic mimicry through directly binding YBX1

Abstract: Vasculogenic mimicry (VM) gives rise to tumor neovascularization that is critical for tumor growth and metastasis. Long non-coding RNAs (lncRNAs) have been implicated in diverse and fundamental biological processes. LINC00312 is associated with lung adenocarcinoma. In this study, we found that LINC00312 induced migration, invasion and VM of lung cancer cells by direct binding to the transcription factor Y-Box Binding Protein 1 (YBX1). Moreover, we demonstrated that YBX1 is associated with different fragments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 10 publications
3
82
0
Order By: Relevance
“…In lung adenocarcinoma, LINC00312 was found to regulate migration, invasion, and VM processes of lung cancer cells. LINC00312 directly binds to the transcription factor Y-box binding protein 1 (YBX1) to regulate VM formation [26]. In ovarian cancer, miR-200a and miR-27b have been reported to be significantly downregulated, and their expression levels were inversely correlated with VM formation.…”
Section: Non-coding Rnas As Emerging Regulators In Tumor Vm Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In lung adenocarcinoma, LINC00312 was found to regulate migration, invasion, and VM processes of lung cancer cells. LINC00312 directly binds to the transcription factor Y-box binding protein 1 (YBX1) to regulate VM formation [26]. In ovarian cancer, miR-200a and miR-27b have been reported to be significantly downregulated, and their expression levels were inversely correlated with VM formation.…”
Section: Non-coding Rnas As Emerging Regulators In Tumor Vm Formationmentioning
confidence: 99%
“…There are several potential mechanisms of VM formation, such as epithelial-mesenchymal transition (EMT) and cancer stem cells (CSCs) [22,23], and various signaling pathways that promote VM formation, including vascular endothelial (VE)-cadherin, erythropoietin-producing hepatocellular receptor A2 (EphA2), phosphatidyl inositol 3-kinase (PI3K), matrix metalloproteinases (MMPs), vascular endothelial growth factor receptor (VEGFR1), cyclic adenosine monophosphate (cAMP), focal adhesion kinase (FAK), and hypoxia inducible factor (HIF)-1a [24,25]. Moreover, noncoding RNAs such as lncRNAs and miRNAs play critical roles in VM formation in malignant tumors [16,[26][27][28]. In this review, we provide new insights into the complexity of vasculogenic mimicry and summarize the latest findings of VM formation in malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating data show that down-regulation of lncRNA NKILA or up-regulation of XLOC_008466 and FAL1 is linked to lymph node metastasis and TNM stage, 12,13,15 and lncRNA AFAP1-AS1, linc00673 and PVT1 predict a poor prognosis in NSCLC. 10,16,17 lncRNA DLEU2 is identified to have a differential expression in LAC, 20 acute myeloid leukaemia 21 and laryngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…oncogenes 11,12 or anti-oncogenes in NSCLC. 6,13 LncRNA AFAP1-AS1, linc00460 and LINC00312 facilitate the proliferation, invasion and epithelial-mesenchymal transition, 5,11,12 while EPB41L4A-AS2 6 and NKILA 13 have the opposite effects in NSCLC cells.…”
mentioning
confidence: 99%
“…LncRNA HOXA-AS2 IGF2 57 LncRNA Myocardial infarction-associated transcript (MIAT) TDP43 58 LncRNA PXN-AS1-L PXN 59 LncRNA LINC00312 Y-Box Binding Protein 1 (YBX1) 60 LncRNA LINC00707 CDC42 61 LncRNA MALAT1 TDP43 62 PTEN/AKT and Akt/mTOR. Recent studies confirmed that many LncRNAs could exert their regulating NSCLC metastasis function by influencing the transduction of different signal pathways.…”
Section: Oncogenic Lncrnas Target Proteins Referencementioning
confidence: 99%